Developing methods based on the use of the Plotagon Story application in teaching Arabic - Agita yurinda Hasibuan, Agita; Rahmaini, Rahmaini (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
There are many problems in the learning process, especially with technology-based learning media. Many educators struggle to create learning media, so they still use conventional methods. Such media can be technology-related. Based on the challenges at MTs N 1 Simalungun, one alternative solution is to implement technology-based learning media using the animated video application Plotagon Story. This research uses the R&D (Research and Development) method, which can produce specific products and test their effectiveness with the ADDIE model: Analyze, Design, Develop, Implement, and Evaluate. The research results show that the cumulative percentage of student responses to the learning media reached 91%, categorized as very interesting, and it has the potential to bring innovation to Arabic language learning.